Intracellular zinc in insulin secretion and action: a determinant of diabetes risk?. Issue 1 (14th September 2015) - Rutter, Guy A.; Chabosseau, Pauline; Bellomo, Elisa A.; Maret, Wolfgang; Mitchell, Ryan K.; Hodson, David J.; Solomou, Antonia; Hu, Ming
Abstract : Zinc is an important micronutrient, essential in the diet to avoid a variety of conditions associated with malnutrition such as diarrhoea and alopecia. Lowered circulating levels of zinc are also found in diabetes mellitus, a condition which affects one in twelve of the adult population and whose treatments consume approximately 10 % of healthcare budgets. Zn 2+ ions are essential for a huge range of cellular functions and, in the specialised pancreatic β-cell, for the storage of insulin within the secretory granule. Correspondingly, genetic variants in the SLC30A8 gene, which encodes the diabetes-associated granule-resident Zn 2+ transporter ZnT8, are associated with an altered risk of type 2 diabetes. Here, we focus on (i) recent advances in measuring free zinc concentrations dynamically in subcellular compartments, and (ii) studies dissecting the role of intracellular zinc in the control of glucose homeostasis in vitro and in vivo. We discuss the effects on insulin secretion and action of deleting or over-expressing Slc30a8 highly selectively in the pancreatic β-cell, and the role of zinc in insulin signalling. While modulated by genetic variability, healthy levels of dietary zinc, and hence normal cellular zinc homeostasis, are likely to play an important role in the proper release and action of insulin to maintain glucose homeostasis and lower diabetes risk.